Cats differ from other species in their cytokine and antioxidant enzyme response when developing obesity. (24th May 2013) - Hoenig, Margarethe; Pach, Nicole; Thomaseth, Karl; Le, Anh; Schaeffer, David; Ferguson, Duncan C.
Abstract : Objectives : Obese cats show many similarities to obese people, including insulin resistance and an increased diabetes risk. However, atherosclerosis and cardiovascular disease are not seen in cats. In people, they are associated with the development of an inflammatory response, which, we hypothesized, does not occur in cats. Design and Methods : Twenty neutered cats of equal gender distribution were allowed to gain weight by offering food ad libitum and were examined before and at 10, 30, 60, and 100% weight gain. All cats reached 60% of weight gain, 12 cats gained 100 % in 12 months. Results : Fat was equally distributed between subcutaneous and visceral depots. Insulin‐independent glucose uptake increased and insulin sensitivity decreased with increasing adiposity. However, baseline glucose concentrations were unchanged suggesting a decrease in EGP. Inflammatory cytokines (Il‐1, IL‐6, TNFa) and catalase, superoxide dismutase, glutathione peroxidase did not change. Insulin, proinsulin, and leptin were positively and adiponectin negatively correlated with adiposity. Heat production increased with obesity, but became less when body weight gain was > 60 %. Conclusions : This indicates that metabolism adapts more appropriately to the higher intake of calories in the initial phase of obesity but slows at higher body fat content. This likely contributes to the difficulty to lose weight.